Novel Variation in CFB Adult Onset Atypical Hemolytic Uremic Syndrome: A Case Report and Review - Chhakchhuak, Malsawmkima (Indian J Nephrol, 2020)
We report a case of 47-year-old male with atypical hemolytic uremic syndrome (aHUS). He had low C3 levels and whole exome sequencing revealed heterozygous missense novel variation in exon 8 of the gene encoding complement factor B (CFB), leading to substitution of leucine for proline at codon 369 (c.1106C>T; p.Pro369Leu). Following plasma exchanges and hemodialysis, the patient achieved hematological remission and became dialysis independent.